Studi Daya Tahan Aerobik Siswa Sekolah Menengah Pertama - Yuni Astuti; Erianti Erianti; Andika Prajana; Zulbahri Zulbahri; Ali Mardius (STKIP PGRI Jombang, 2021)
The problem in this research is unknown aerobic endurance students of SMP Negeri 2 Painan South Coastal District. In accordance with these problems, then the purpose of this study was to determine the aerobic endurance students of SMP Negeri 2 Painan South Coastal District. This kind of research is descriptive. The population in this study are all students of SMP Negeri 2 Painan South Coastal District numbered as many as 151 people. The sampling technique used purposive sampling. Thus the sample in this study amounted to as many as 43 people. To obtain the data to judge the aerobic endurance. Data were analyzed using percentages. The research result found that: (1) female students, none of the 26 students who have a good aerobic endurance categories at all, 8 people both categories, 13 categories and 5 categories were less so. This means that most of the male students sampled not good aerobic endurance. (2) Male students, of 17 students found each two students have aerobic endurance excellent and good categories, 9 and 4 categories were less category. This means that many female students as well who do not have a good aerobic endurance.